PENGARUH PRODUCT DIFFERENTATION, HARGA DAN FASILITAS TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA IGLOO DESERT BAR ITALIAN GELATO SANGATTA - Theresia Stefania Kewa Kuwa; RR Tri Gunarti; Irma Irma (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2026)
The research aims to determine the effect of product differentiation, price and facilities on consumer purchase decisions of Igloo Desert Bar Italian Gelato Sangatta. This research method. The data used were primary data obtained from distributing questionnairesto consumer of Igloo Desert Bar Italian Gelato Sangatta. Residential real estate, with a sample of 96 respondents. At the same time, data analysis technique used multiple linear regression. The finding denoted that partially and simultaneously, product differentiation, prices and facilities variable affected significant the purchase decisions of Igloo desert Bar Italian Gelato Sangatta. The simultaneous effect of product differentiation, prices, and facilities variables on purchase decisions was 0,000 < 0,05, on the other hand, the partially effect of the product differentiation variable on purchase decisions was 46,81%, the partially effect of the price variable on purchase decisions was 33,48%, and the effect of the facilities variable on the purchase decision was 38,89%.